2023
DOI: 10.1108/ijoem-05-2022-0815
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow climate pact and the global clean energy index constituent stocks

Abstract: PurposeThis study examined the impact of the Glasgow Climate Pact on the abnormal returns of global clean energy stocks. Further, this study examines which country-specific and firm-specific variables drive the cumulative abnormal returns (CARs) of clean energy stocks.Design/methodology/approachThe authors used the event study method and cross-sectional multivariate regression model. The clean energy stocks in this study are limited to 81 constituent firms of the S&P Global Clean Energy Index across 17 nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Several recent studies have utilized event study methodology to investigate the effects of various events on different financial markets (Abbassi et al, 2023;Boubaker et al, 2015;Chortane and Pandey, 2022;Goodell and Huynh, 2020;Goyal and Soni, 2023;Jaiswal and Dubey, 2022;Kumari et al, 2023a, b;Pandey et al, 2023a;Pandey and Kumari, 2021;Rai and Kumari, 2022). Following it, the present study employed the most widely used market model of event study methodology (Buigut and Masinde, 2022;Kumari et al, 2023a, b;Pandey et al, 2023c;Pandey and Kumari, 2022) to explore the impact of the event on the Indian banking and financial services sector stocks. The timeline of the event study consists of an estimation window of 200 trading days from tÀ207 to tÀ8 and a 15-day event window (À7, þ7) (Pandey et al, 2023a) 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have utilized event study methodology to investigate the effects of various events on different financial markets (Abbassi et al, 2023;Boubaker et al, 2015;Chortane and Pandey, 2022;Goodell and Huynh, 2020;Goyal and Soni, 2023;Jaiswal and Dubey, 2022;Kumari et al, 2023a, b;Pandey et al, 2023a;Pandey and Kumari, 2021;Rai and Kumari, 2022). Following it, the present study employed the most widely used market model of event study methodology (Buigut and Masinde, 2022;Kumari et al, 2023a, b;Pandey et al, 2023c;Pandey and Kumari, 2022) to explore the impact of the event on the Indian banking and financial services sector stocks. The timeline of the event study consists of an estimation window of 200 trading days from tÀ207 to tÀ8 and a 15-day event window (À7, þ7) (Pandey et al, 2023a) 1.…”
Section: Methodsmentioning
confidence: 99%
“…Following it, the present study employed the most widely used market model of event study methodology (Buigut and Masinde, 2022; Kumari et al. , 2023a, b; Pandey et al. , 2023c; Pandey and Kumari, 2022) to explore the impact of the event on the Indian banking and financial services sector stocks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their final findings, Bai et al (2023) found that the green energy Sharp ratios within the CNB have their level of significance greater than other stocks in different method of allocations (Bai, et al, 2023). Pandey, et al (2023) analysed the effect of the Glasgow Climate Pact (GCP) on the stock returns of world clean energy stocks. They further examined how and if some firm-specific factors and countryrelated factors contribute to influence the aggregate stock returns of clean energy.…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%